Orthodontic management of buccally erupted ectopic canine in a 12 year-old child - Kumar, Sagarika; Kumar, Arvind; Shikha, Smriti; Singh, Aparna; N., Ruqaia Banu (International Journal of Research in Medical Sciences, 2025)
Ectopic teeth are teeth that develop displaced from their normal position. Any permanent tooth can be ectopic, and the cause may be both genetic and environmental. Ectopic buccally erupted maxillary canines are one of the most frequently encountered conditions because of its long path of eruption. Re positioning of these tooth is important because ectopic canine teeth can migrate in the jaw bone and may damage the adjacent teeth roots and bone. Treatment is also justifiable for aesthetic reasons. Diagnosis and treatment of ectopically erupting permanent maxillary canines requires timely management by the orthodontist. Internal or external root resorption of teeth adjacent to the ectopic canine is the most common sequel. Malocclusion with severe crowding is difficult to treat without extraction. Non-extraction treatment of ectopic canines can compromise the patient's profile. This article presents a cases of extraction treatment approach for buccally displaced or ectopic canine in a patient.